Analysis of anxiety depending on the status of complications in patients with diabetes mellitus - Milanović, Ana; Pucar, Aleksandra; Mehmedović, Amin; Mladenović, Danilo; Kotur, Milica (Medicinski podmladak, 2025)
Introduction: Anxiety disorders are one of the leading types of disorders in the general population whose symptoms often have a significant impact on people’s daily lives. Additionally, anxiety symptoms have been shown in studies conducted around the world to be a significant factor that affects the course of diabetes, as well as the development of possible complications of the disease itself. Aim: The aim of this work is to examine the impact of anxiety symptoms on diabetic foot complications in the Serbian population in order to see the need for psychological support as a form of prevention of this type of complication. Material and methods: This research is a retrospective-prospective study conducted in the period from October 15, 2023. until February 15, 2024. The study included 87 patients divided into three groups depending on the status of complications of diabetes mellitus. All subjects were patients of the Endocrinology Clinic University Clinical Center of Serbia (UCCS) and the Institute of Orthopedic Surgery and Traumatology UCCS. Respondents were surveyed with the GAD-7 (General Anxiety Disorder-7) questionnaire. Data on gender, age, duration of illness, complications and comorbidities were collected for all subjects. Statistical analysis was performed in the program EZR: R Commander. Results: The analysis showed that there is a statistically significant difference in the results of the GAD-7 test between the group of patients with amputations and the control group, as well as the group of patients with amputations and the group on conservative treatment, while there is no statistical difference between the control group and the group whose diabetic foot is treated conservatively. Conclusion: The results of our study indicate the possible influence of anxiety on the development of diabetes mellitus in patients as well as on the faster progression of the disease itself and the possible need for support for certain patients. Keywords: anxiety, diabetes mellitus, diabetic foot